Anticipatory Governance dalam Manajemen Kebencanaan: Transformasi Pemerintah Daerah Kabupaten Lombok Tengah dari Respons Darurat Menuju Tindakan Pra-Bencana - Mujahidin; Lalu Ahmad Murdhani (IPDN Kampus NTB, 2025)
This study aims to analyze the transformation of disaster management in the Local Government of Central Lombok Regency from emergency response toward pre-disaster action through an anticipatory governance approach. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, field observation, focus group discussions, and document analysis involving actors engaged in disaster management, including local government, the Regional Disaster Management Agency, related local agencies, village governments, local communities, volunteers, academics, private sector actors, and civil society organizations. The data were analyzed thematically through data reduction, theme categorization, data presentation, interpretation, and conclusion drawing. The findings reveal that disaster management in Central Lombok remains largely oriented toward emergency response, particularly in resource mobilization, coordination, and decision-making after disasters occur. Anticipatory capacity has begun to emerge through risk documents, early warning systems, and preparedness programs, but it has not been fully integrated into development planning, budgeting, and cross-sectoral coordination. The main contribution of this study is the formulation of an anticipatory governance model consisting of six components: risk and vulnerability mapping, impact-based prediction and early warning systems, pre-disaster action triggers, cross-sectoral coordination, pre-disaster financing and resource activation, and institutional evaluation and learning. This model emphasizes the need for local governments to shift from waiting for disaster impacts to reading risks and acting before disasters occur.